Monetary policy committee transparency: Measurement, determinants, and economic effects - Bernd Hayo; Ummad Mazhar (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper studies monetary policy committee transparency (MPCT) based on a new index that measures central bankers' educational and professional backgrounds as disclosed through central bank websites. Based on a novel cross-sectional data set covering 75 central banks, we investigate the determinants of MPCT as well as its economic consequences. We find that past inflation, quality of institutional setup, and extent of Internet use in a country are important determinants of MPCT. MPCT has a robust and significantly negative impact on inflation variability, even after controlling for important macroeconomic variables and institutional transparency, as well as instrumenting MPCT in various ways.
Keywords: E52; E58; D12; D83; 330; monetary policy committee; transparency; monetary policy transparency; monetary policy; central banks; Zentralbank; Geldpolitik; Gruppenentscheidung; Informationsverhalten; Staatliche Information; Wirkungsanalyse; Inflation; Welt